Long-term drug treatment in multiple sclerosis: safety success and concerns. Issue 9 (1st September 2020) - Jakimovski, Dejan; Vaughn, Caila B; Eckert, Svetlana; Zivadinov, Robert; Weinstock-Guttman, Bianca
ABSTRACT: Introduction: The portfolio of multiple sclerosis (MS) disease modifying treatments (DMTs) has significantly expanded over the past two decades. Given the lifelong use of MS pharmacotherapy, understanding their long-term safety profiles is essential in determining suitable and personalized treatment. Areas covered: In this narrative review, we summarize the short-, mid-, and long-term safety profile of currently available MS DMTs categories. In addition to the initial trial findings, safety outcomes derived from long-term extension studies (≥5–20 years) and safety-based prescription programs have been reviewed. In order to better understand the risk-benefit ratio for each particular DMT group, a short description of the DMT-based efficacy outcomes has been included. Expert opinion: Long-term extension trials, large observational studies and real-world databases allow detection of rare and potentially serious adverse events. Two-year-long trials are unable to fully capture the positive and negative effects of immune system modulation and reconstitution. DMT-based monitoring programs can provide greater insights regarding safe use of MS medications in different patient populations and clinical settings. During the process of shared DMT decision, both MS care providers and their patients should be aware of an ever-expanding number of drug-based adverse events and their influence on the risk-benefit analysis.